Mental Health Needs of Adolescents Assessed During the Years of Global Financial Crisis: a Systematic Review - Sakellari Evanthia; Athanasopoulou Christina; Kokkonen Pinja; Leino-Kilpi Helena (Avicena, 2022)
Introduction: Mental health issues during adolescence are common and worsen when financial crisis occur across the world. Identification of mental health needs as they are expressed by adolescents themselves is important for efficient mental health promotion interventions. Aim: This systematic review examined studies on the mental health needs among adolescents from their own perspective. Methods: Four databases were searched between 2008-2018, starting with 2008 when the global financial crisis began. Results: The seven studies that fulfilled the inclusion criteria used different data collection methods. Emotional and behavioral problems and hyperactivity were found, while adolescents’ own perceptions also showed positive indicators for mental health. Most studies focus on specific adolescent populations, while the general adolescent population needs more attention as a target group for mental health interventions. Conclusion: Interventions should address the needs as they are identified by adolescents in order to promote their mental health. Researchers should develop an instrument which assesses exclusively the adolescents’ mental health needs.